Comparative-genomic analysis reveals dynamic NLR gene loss and gain across Apiaceae species - Liang, Xiaohui; Dong, Junming (Frontiers in Genetics, 2023)
Nucleotide-binding leucine-rich repeat (NLR) genes play a crucial role in green plants’ responding to various pathogens. Genome-scale evolutionary studies of NLR genes are important for discovering and applying functional NLR genes. However, little is known about the evolution of NLR genes in the Apiaceae family including agricultural and medical plants. In this study, comparative genomic analysis was performed in four Apiaceae species to trace the dynamic evolutionary patterns of NLR genes during speciation in this family. The results revealed different number of NLR genes in these four Apiaceae species, namely Angelica sinensis (95), Coriandrum sativum (183), Apium graveolens (153) and Daucus carota (149). Phylogenetic analysis demonstrated that NLR genes in these four species were derived from 183 ancestral NLR lineages and experienced different levels of gene-loss and gain events. The contraction pattern of the ancestral NLR lineages was discovered during the evolution of D. carota, whereas a different pattern of contraction after first expansion of NLR genes was observed for A. sinensis, C. sativum and A. graveolens. Taken together, rapid and dynamic gene content variation have shaped evolutionary history of NLR genes in Apiaceae species.